PELATIHAN KEWIRAUSAHAAN MELALUI USAHA KREATIF DAN INOVATIF MASYARAKAT DESA TEGAL SARI KECAMATAN MEGANG SAKTI KABUPATEN MUSI RAWAS - Agung Nugroho; Rusni Eka Putra; Ahmad Amin (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2018)
The purpose of the author to do this PKM is entrepreneurship training in making shredded oyster mushrooms and marketing them online in the village of Tegal Sari, Megang Sakti District, Musi Rawas Regency. The problem in this PKM is "How to improve the ability to process village natural resources and market them online in the community of Tegal Sari Village, Megang Sakti District, Musi Rawas Regency? The dominant problem that arises in Tegal Sari Village is the lack of maximum processing of abundant natural resources due to the low human resources of the community. The method used in this training activity is the training method which includes discussion, question and answer, and practice. Based on the results of PKM activities in Tegal Sari Village, it can be concluded that entrepreneurship training activities run well, by producing processed oyster mushrooms in the form of abon and marketing them traditionally and online in the Musi Rawas Regency and surrounding areas.